معيار الحيل والمخارج في الفقه الإسلامي: Shariah status of legal artifices and legal devices - Dr. Muhammad Asad (MEI, 2023)
This article discusses the shariah status of legal artifices and legal devices. As it is difficult to differentiate between the legal artifices and legal devices, therefore they are being misused by the people. This article enables the reader to distinguish between legal artifices and legal devices and avoid from the misuse of legal artifices. The article contains the three parts: first part contains the meaning of legal artifices and legal devices and differences between them send part contains the kinds of legal artifices and third part contains the opinions of classical scholars about the shariah status of legal artifices.